An empirical analysis of software practices in Malaysian Small and Medium Enterprises - Almomani, M.A. (Institute of Electrical and Electronics Engineers Inc., 2016)
Small and Medium Enterprises are growing rapidly and becoming a key component in the industrial profile in many countries around the world. Therefore, good organizational management practices are strongly affected by the organizational performance. Unfortunately, there has been little empirical evidence about organizational management practices through Small and Medium Enterprises, especially in the Southeast Asian region. Hence, the main purpose of this paper is to investigate the current level of software development practices through Malaysian Small and medium Enterprises from an organizational perspective. The researchers conducted a survey of seventeen companies which are specialized in software development. The results indicated that Malaysian small and medium software companies still in the low level of organizational management practices. Finally, the present study helps senior managers in order to be realize and aware about the shortcoming issues whilst providing clear vision to develop comprehensive strategies to improve organization performance in Malaysian SME companies. Â© 2016 IEEE.